ปัจจัยที่มีผลต่อการตัดสินใจเข้าร่วมการจัดงานไม้แกะสลักประจำปีของประชาชนในอำเภอแม่ทา จังหวัดลำพูน - ธีรทัศน์ ศักดิ์กุลเจริญ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This study on “Factors Affecting the People’s Decision on Participation in Wood Handicraft Exhibition in Mae Tha District, Lamphun Province” had the objectives of 1) learning about the general condition of the members of the craftsmen group in Mae Tha District of Lamphun Province; 2) finding the factors affecting their decision to participate in the annual wood handicraft exhibition in Mae Tha District and 3) examining the attitude of the entrepreneurs on the exhibition. The study involved 500 people in the sample group of wood carvers and entrepreneurs in the study area using questionnaires as the tool to collect the data in 3 parts: 1) personal information, 2) factors affecting their decision to participate in the annual wood handicraft exhibition in Mae Tha District, and 3) the entrepreneurs’ attitude about the decision to participate in the annual exhibition of wood carving products. The data was analyzed using a statistical program and the following results were obtained. 1) Their main occupation as wood carvers or those dealing with the wood carving business was the most important factor for them to gain a higher chance of 81.34 percent to participate in the exhibition. 2) The people’s experience in wood carving served as the second most important factor for their decision in participating in the exhibition. With at least 10 years of wood carving experience, the chance of their participation would increase by 41.30 percent. 3) The sample group’s attitude about attracting tourists and shoppers to the area had a negative correlation coefficient which indicated that people who were not tourists and shoppers had a higher chance of participating in the wood carving exhibition. This factor would lead to a 41.86 percent increase in the likelihood of people to participate. 4) The gender of the sample group was a significant factor in affecting the people’s decision in participating in the wood carving exhibition. A 99 percent confidence interval indicated that males were more likely to participate in the exhibition than females. The chance increase was 21.73 percent. 5) Marital status was a significant factor in affecting the people’s decision in participating in the wood carving exhibition. A 90 percent confidence interval indicated a 17.46 percent increase in chance of exhibition participation for those who are married. 6) Satisfaction in revenue generated from organizing the exhibition was a significant factor in affecting the people’s decision in participation. A 90 percent confidence interval indicated that people experience satisfaction from other factors not limited to revenue generated from organizing the exhibition. This led to a 28.49 percent increase in chance of people deciding to participate in the wood carving exhibition at Mae Tha district. 7) The sample group’s perception of increasing public awareness of the wood carving exhibition was a significant factor in affecting the people’s decision in participation. A 90% confidence interval indicated that the wood carving exhibition was popular amongst the public. This led to a 24.96 percent increase in chance of people deciding to participate in the wood carving exhibition at Mae Tha district. The study revealed the following problems: 1) wood used for carving violated forest protection laws; 2) high production costs; 3) expensive selling prices due to high production costs limited the target market to high income customers, where middle and low income customers have no purchasing power to afford the products; 4) tourists’ perception of wood carving products in Mae Tha district as more expensive than those at Baan Tawai, Chiang Mai province, reduced the revenue generated from the exhibition; 5) increased scarcity of talented craftsmen due to career shifts.